Deaf and hard of hearing in the United Arab Emirates interacting with Alexa, an intelligent personal assistant. - Shahin, Nada; Watfa, Mohamed (Technology & Disability, 2020)
BACKGROUND: Intelligent Personal Assistants have been booming around the world since 2014, allowing millions of users to interact with different cloud-based software via speech. Unfortunately, the Deaf and Hard of Hearing individuals have been left out without recognizable accessibility to such technologies, although it might be used to make their daily life routine easier. OBJECTIVE: In this research, the researcher studies the interaction and perception of Amazon's Alexa among the Deaf and Hard of Hearing in the United Arab Emirates in its current set up (Tap-to-Alexa accessibility option) in addition to Sign Language as an input method. The researcher expands on the Technology Acceptance Model to study the acceptance of Alexa as an assistive technology for the Deaf and Hard of Hearing. Additionally, the researcher discusses more suitable input methods and solutions to allow Alexa, and other Intelligent Personal Assistants, be more accessible for the Deaf and Hard of Hearing. METHODS: The mixed method is used in this research in terms of collecting primary data through hands-on experiments, surveys, and interviews with the Deaf and Hard of Hearing participants. RESULTS: The researcher found that the Deaf and Hard of Hearing in the United Arab Emirates perceive that Sign Language combined with a Live interpreter is better than the accessibility option "Tap-to-Alexa", which is a solution provided by Amazon. The researcher also found that Sign Language combined with a Live interpreter is the most suitable input method to make the device accessible for the Deaf and Hard of Hearing, in addition to translating the "Tap-to-Alexa" to different languages. Finally, the researcher proposes a modification to the Technology Acceptance Model to suit the research study of the Deaf and Hard of Hearing perception of Alexa. CONCLUSIONS: The researcher concludes that the ideal scenario for the Deaf and Hard of Hearing to interact and benefit the most from Amazon's Alexa, and IPAs in general, is to include Sign Language as an embedded input method in the device and provide live interpreters; this sheds light on the importance of the interpreters' jobs around the world. Additionally, "Tap-to-Alexa" must be translated into different languages for a better perception of the input method.